2020
DOI: 10.11610/connections.19.2.08
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in the Central Asian Region: National Responses and Regional Implications

Abstract: Soon after the first instance of COVID-19 in Central Asia was recorded in March 2020 in Kazakhstan, the government took immediate steps to introduce containment and mitigation measures. As cases of COVID-19 appeared soon afterwards in Uzbekistan, Kyrgyzstan, and later in Tajikistan, the governments swiftly responded, instituting emergency measures, empowering law enforcement and medical authorities to implement a broad range of counter-infection mitigation measures to protect public health. Cross-border travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Kyrgyzstan is a developing country and the national currency value heavily depends on exports of raw materials, gold and income of migrants working abroad. 22,4% of the population live below poverty line [ 7 ] and large number of people are self-employed and are not covered by social protection that official employees have [ 11 ]. The quarantine restrictions implemented by Kyrgyzstan and neighboring countries expect to lead to 4% drop in GDP by the end of 2020.…”
Section: Peak Of the Wavementioning
confidence: 99%
See 1 more Smart Citation
“…Kyrgyzstan is a developing country and the national currency value heavily depends on exports of raw materials, gold and income of migrants working abroad. 22,4% of the population live below poverty line [ 7 ] and large number of people are self-employed and are not covered by social protection that official employees have [ 11 ]. The quarantine restrictions implemented by Kyrgyzstan and neighboring countries expect to lead to 4% drop in GDP by the end of 2020.…”
Section: Peak Of the Wavementioning
confidence: 99%
“…This is exacerbated by plummeting business activities in production textile and tourism [ 5 ]. Many financial international institutions lined-up to provide aid, but the scale and scope of the assistance will not suffice to compensate the disastrous economic impact in the long term [ 11 ].…”
Section: Peak Of the Wavementioning
confidence: 99%
“…Uzbekistan improved its position in terms of openness and foreign exposure since 2016. The lucky escape from the SARS outbreak in 2003 lead authorities a wrong assumption of having appropriate system in place in case of pandemics (1). The biggest challenge that Uzbekistan faced was lack of preparedness in terms of healthcare responsiveness and agility.…”
Section: Business Continuity Planning and Civic Responsementioning
confidence: 99%
“…The first signals of upcoming coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection from Wuhan city of China have been received worldwide at the end of December 2020 (1). The world-leading news agencies started monitoring China's situation and in January reported that Wuhan City faced a lockdown and its citizens were required to stay at home to stop the spread of the coronavirus (2) it is reviewed as the most effective measure (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation